2014
DOI: 10.1093/ntr/ntu196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Puff Topography, Toxicant Exposure, and Subjective Effects in Low- and High-Frequency Waterpipe Users: A Double-Blind, Placebo-Control Study

Abstract: Higher frequency waterpipe users may be more sensitive to the effects of waterpipe smoke nicotine content. Among HIGH users, higher baseline nicotine/tobacco abstinence symptoms may indicate greater nicotine dependence. These data support continued surveillance of WTS and development of dependence measures specific to this product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Advantages of these methods are that they are time- and cost-efficient relative to longer-term studies, and can be predictive of the results of those studies (e.g., Breland et al, 2002; Fagerström et al, 2000, 2002; Hughes and Keely, 2004). The effects reported in these studies are also reliable, as has been demonstrated previously for a “heat, not burn” product (Buchhalter and Eissenberg, 2000; Buchhalter et al, 2001; Breland et al, 2002) and for tobacco smoking using a waterpipe (Blank et al, 2011; Cobb et al, 2015, 2011) and as highlighted by comparing the ECIG effects reported here with those that were reported elsewhere using an identical device/liquid combination (Lopez et al, 2016). That is, in this study and that reported by Lopez et al (2016), cigarette-smoking participants completed two, 10-puff (30 sec interpuff interval) use bouts with an ECIG composed of a 3.3 V battery attached to a 1.5 Ohm dual-coil heating element loaded with approximately 1 ml of a 18 mg/ml nicotine liquid made of approximately 70% propylene glycol and 30% vegetable glycerin.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Advantages of these methods are that they are time- and cost-efficient relative to longer-term studies, and can be predictive of the results of those studies (e.g., Breland et al, 2002; Fagerström et al, 2000, 2002; Hughes and Keely, 2004). The effects reported in these studies are also reliable, as has been demonstrated previously for a “heat, not burn” product (Buchhalter and Eissenberg, 2000; Buchhalter et al, 2001; Breland et al, 2002) and for tobacco smoking using a waterpipe (Blank et al, 2011; Cobb et al, 2015, 2011) and as highlighted by comparing the ECIG effects reported here with those that were reported elsewhere using an identical device/liquid combination (Lopez et al, 2016). That is, in this study and that reported by Lopez et al (2016), cigarette-smoking participants completed two, 10-puff (30 sec interpuff interval) use bouts with an ECIG composed of a 3.3 V battery attached to a 1.5 Ohm dual-coil heating element loaded with approximately 1 ml of a 18 mg/ml nicotine liquid made of approximately 70% propylene glycol and 30% vegetable glycerin.…”
Section: Discussionsupporting
confidence: 87%
“…A fourth implication of this work is that clinical laboratory methods such as those described here and also used to evaluate other novel tobacco products (Buchhalter et al, 2001; Breland et al, 2002; Cobb et al, 2015, 2010; Gray et al, 2008; Lopez et al, 2016) are valuable for revealing important features of these products, including toxicant delivery and physiological and subjective effect profile. Advantages of these methods are that they are time- and cost-efficient relative to longer-term studies, and can be predictive of the results of those studies (e.g., Breland et al, 2002; Fagerström et al, 2000, 2002; Hughes and Keely, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The majority of participants in this study were regular WP smokers, but did not report high levels of dependence. Existing research suggests high and low frequency WP smokers differ in terms of their attitudes and beliefs about WP smoking47 as well as in their smoking patterns and behaviours 46. For this reason, the current study may not generalise to more frequent or nicotine dependent WP smokers.…”
Section: Discussionmentioning
confidence: 85%
“…However, one recent study compares the effects of a 12 h abstinence period in frequent (≥20 monthly episodes, n=17) and occasional (2–5 episodes monthly; n=63) users. 104 While the relatively small sample size in the frequent user group may have influenced study sensitivity adversely, elevated scores on several withdrawal-related measures were observed in the frequent users relative to the occasional users (eg, both factors of the modified Questionnaire of Smoking Urges). Interpreting these results is made challenging by the absence of an assessment of participant dependence using a validated scale (eg, the LWDS-11).…”
Section: Does the Literature On Wts Address Key Features Of Dependencmentioning
confidence: 99%